Suomi NPP CrIS measurements, sensor data record algorithm, calibration and validation activities, and record data quality. Issue 22 (25th November 2013) - Han, Yong; Revercomb, Henry; Cromp, Mike; Gu, Degui; Johnson, David; Mooney, Daniel; Scott, Deron; Strow, Larrabee; Bingham, Gail; Borg, Lori; Chen, Yong; DeSlover, Daniel; et al.
Abstract [1] The Cross‐Track Infrared Sounder (CrIS) is a Fourier Transform Michelson interferometer instrument launched on board the Suomi National Polar‐Orbiting Partnership (Suomi NPP) satellite on 28 October 2011. CrIS provides measurements of Earth view interferograms in three infrared spectral bands at 30 cross‐track positions, each with a 3 × 3 array of field of views. The CrIS ground processing software transforms the measured interferograms into calibrated and geolocated spectra in the form of Sensor Data Records (SDRs) that cover spectral bands from 650 to 1095 cm−1, 1210 to 1750 cm−1, and 2155 to 2550 cm−1 with spectral resolutions of 0.625 cm−1, 1.25 cm−1, and 2.5 cm−1, respectively. During the time since launch a team of subject matter experts from government, academia, and industry has been engaged in postlaunch CrIS calibration and validation activities. The CrIS SDR product is defined by three validation stages: Beta, Provisional, and Validated. The product reached Beta and Provisional validation stages on 19 April 2012 and 31 January 2013, respectively. For Beta and Provisional SDR data, the estimated absolute spectral calibration uncertainty is less than 3 ppm in the long‐wave and midwave bands, and the estimated 3 sigma radiometric uncertainty for all Earth scenes is less than 0.3 K in the long‐wave band and less than 0.2 K in the midwave and short‐wave bands. The geolocation uncertainty for near nadir pixels is less than 0.4 km in the cross‐track and in‐track directions.